2021
DOI: 10.1088/1755-1315/839/2/022095
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary global production and consumption of cocoa: an assessment

Abstract: The paper is dedicated to an analysis of the production of cocoa, which is a critical component for many sectors of the economy. Scientists on a regular basis identify new valuable properties of cocoa, and the scope of its application expands accordingly. Since the 1960s, the global production of cocoa beans has grown fivefold. The key areas of production of the crop include Africa, America, Asia and Oceania. The three countries that in 2019 accounted for almost 60% of the production were Ghana, Cote d’Ivoire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…As the demand of cocoa beans and its products increasing (Gu et al, 2011), it is impacted to the challenges coped by cocoa beans industry to boost production (Akinlabi et al, 2019). Limited supply and inconsistent production of cocoa beans becoming challenge for the cocoa industry (Gavrilova, 2021;Geo & Saediman, 2019). Several factors that cause these are low quality of human resources, lack of access to finance and inadequate infrastructure (Indah et al, 2018), pest and disease attacks (EU et al, 2022), deforestation and loss of biodiversity (Renier et al, 2023), the threat of climate change (Igawa et al, 2022) and fairness in the cocoa supply chain (Krauss & Barrientos, 2021).…”
Section: The Impact Of Production Challenges On the Cocoa Beans Industrymentioning
confidence: 99%
“…As the demand of cocoa beans and its products increasing (Gu et al, 2011), it is impacted to the challenges coped by cocoa beans industry to boost production (Akinlabi et al, 2019). Limited supply and inconsistent production of cocoa beans becoming challenge for the cocoa industry (Gavrilova, 2021;Geo & Saediman, 2019). Several factors that cause these are low quality of human resources, lack of access to finance and inadequate infrastructure (Indah et al, 2018), pest and disease attacks (EU et al, 2022), deforestation and loss of biodiversity (Renier et al, 2023), the threat of climate change (Igawa et al, 2022) and fairness in the cocoa supply chain (Krauss & Barrientos, 2021).…”
Section: The Impact Of Production Challenges On the Cocoa Beans Industrymentioning
confidence: 99%
“…Cocoa ( Theobroma Cacao L.) is the basic raw material to produce chocolate and other derivatives such as cocoa butter, cocoa powder and cocoa liquor (cocoa paste) [1], which has sustained part of the daily diet of people and is currently making inroads in the cosmetics, perfumery and pharmaceutical industries [2] with a requirement in the final quality of the product. Recent studies have reported that grain quality in sensory terms is affected by different factors such as the genetics of the material [3], environmental conditions [4], the state of maturity of the grain and practices in the postharvest stage [5], such as those related to fermentation and drying [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa cultivation occupies a prominent place in the world economy because this fruit generates important products for various segments such as confectionery, dairy, and alcoholic beverages, as well as the pharmaceutical, cosmetic, and perfumery sectors [1,2]. The emergence of new demands, such as fine chocolates, as well as the description of various functional effects of biomolecules present in cocoa, should drive the continued growth of cocoa production in the coming years [3].…”
Section: Introductionmentioning
confidence: 99%